Female Mortality Disadvantage in India - Hanson, Carly; Hubbard, Rebecca (My University, 2012)
Sons are considered more valuable than daughters in India, due to a strong patriarchal society. This preference often ensures sons a higher chance of survival than daughters. A girl may suffer from significant mortality disadvantages such as prenatal sex selection and post-natal discrimination, an excess female infant mortality. While female mortality disadvantage creates a large number of missing girls in India, prevalence varies by state. The objective of this study was to estimate the number, percentage, and source of female mortality disadvantage.
Color poster with text and tables.
Keywords: Sex of children, Parental preferences for--India; Female feticide--India; India--Social life and customs; Posters